Behaviours of Anthracoceros albirostris convexus (Temminck, 1831) in human settlement area, Sungai Panjang, Selangor, Malaysia - Mohd Jamil, Nurulhuda (2013)
The research was conducted in Kampung Parit 13 (N 030 43.512’, E 1010 04.751’), Sungai Panjang situated on the north of Selangor in the District of Sabak Bernam located near the Sungai Karang Forest Reserve. There are four species of sympatric hornbill recorded in the forest namely Rhinoceros Hornbill (Buceros rhinoceros), Bushy-crested Hornbill (Anorrhinus galeritus), Black Hornbill (Anthococeros malayanus) and Oriental Pied Hornbill (Anthracoceros albirostris). This includes one sub species of Oriental pied Hornbill that is the Southern pied Hornbill (Anthracoceros albirostris convexus). Hornbills can be a good indicator of the forest condition and human disturbance. That is because they need large territory for feeding and breeding activities. Therefore, the presence of Southern pied Hornbill (Anthracoceros albirostris convexus) in the nearest village suggest that there is a need to study on their status and behaviour as they attempt to live with the human near the human settlement area. There were three objectives in this study being the first one is to assess this Hornbills’ population size at the study site. Secondly, it is to study the behaviours of Southern pied Hornbill during non-breeding season and finally the behaviours of this bird during their breeding season. Observations were done from February 2009 until April 2011. The study was carried out in 501 hectare of residential area. Six line transects had been set up on certain areas to appraise the population size of this hornbill. Transects were chosen randomly within the study area and are based on available roads or trails. There were 18-visiting times in total for the six transect during non breeding season to estimate the population of this birds in the study area. There is also a rapid observation to identify the increasing number of birds in the area after the breeding season in which, 3-visiting times for Transect 1 and 2 respectively after the breeding season. Both transects were chosen due to the high number of birds in the area compared to the other four transects. During the transect observations, the highest number of birds in group recorded were 24.67±4.16 individuals before breeding season and 28.67±3.06 individuals after the breeding season. It shows that there are new individuals of birds joining the group. From paired sampled test, the number of hornbill in Transect 2 is significantly different (p<0.05) between before breeding season and after breeding season. The population sizes of Southern pied Hornbill estimated in the study area is 24.5 individuals in 501 hectares. The second objective is to study the behaviours of Southern pied Hornbill during the non-breeding season. Meanwhile the third objective is to study the behaviours of Southern pied Hornbill during the breeding season. Both objectives used the same methodology but conducted in different seasons. Their diurnal behaviours during both seasons were observed by intensive focal observations based on sampling blocks. The sampling block is the partition of time made for observation activities. The sampling blocks were used as dependent variable for each of the behavioural recorded and also to differentiate the intensity of each activity during the day. Four selected couples of Southern pied hornbill were chosen to be observed for their daily routines as they attempted to breed in four different locations in clay jars (artificial nest) in the village. Their daily behaviours were accessed by one-way ANOVA (SPSS 18) and were converted into ethogram. The result shows that sampling blocks had significant effect on each of their diurnal behaviour including feeding (F= 121.27, p< 0.001), maintenance (F= 464.31, p<0.001), interaction (F= 17.04, p< 0.001), nest visit (F= 19.35, p< 0.001) and roosting (F= 189.31, p< 0.001) during non-breeding season. Based on ethogram analysis, the birds spend most of their time daily to forage during non-breeding (38.60%) and breeding season (49.23%). Meanwhile diurnal activities recorded for non-breeding season which are interaction of the birds (9.46%), nest visit (12.79%), maintenance activities (15.72%) and roosting (5.81%) are different from breeding season. During the breeding season, the female allocates 42.58% of her time securing and cleaning the nest, while 49.23% of male’s time were used to provide food to feed the inmates and the rest is for his roosting activity (8.18%). This study recorded the nesting periods for this species is 79±10.5 day with estimation of 27±5.5 day of incubation period. Meanwhile, there were about 1.8±0.4 of fledglings success recorded during the study. In general, this study ascertained that Kampung Parit 13 ecosystem is worth to make it as conservation area with ample food supply and an ideal habitat for these hornbills. Moreover, the villager’s acceptability toward this hornbill’s occurrence might somehow aid in promoting public awareness level on their conservation effort. Last but not least, continuous environmental monitoring program should be implemented in Sungai Karang Forest Reserve to reveal the current status of the hornbill present there. It is important to conserve this forest since it is one of the main habitats for these hornbills in Malaysia. Losing of this hornbill will give a negative perception towards our country. At the moment, the results of the study will provide important baseline data as reference for future studies on hornbill’s status and behaviour in human settlement area.